Institute for Scientific Information Chestnut Street office entrance
A black and white photograph depicting the fifth-floor entrance to the Institute for Scientific Information (ISI) Chestnut Street office. The ISI was an academic publishing service, founded by Eugene Garfield (1925-2017) in Philadelphia in 1956. ISI offered scientometric and bibliographic database services and specialized in citation indexing and analysis.
Keywords: Garfield, Eugene; Information science; Information storage and retrieval systems; Citation indexes; Science publishing; Science--Information services; Institute for Scientific Information